2004
DOI: 10.1074/jbc.m400827200
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxin/Munc18 Interactions in the Late Events during Vesicle Fusion and Release in Exocytosis

Abstract: The SNARE proteins, syntaxin, SNAP-25, and VAMP, form part of the core machinery for membrane fusion during regulated exocytosis. Additional proteins are required to account for the speed, spatial restriction, and tight control of exocytosis and a key role is played by members of the Sec1/Munc18 family of proteins that have been implicated either in vesicle docking or fusion itself through their interactions with the corresponding syntaxin. Using amperometry to assay the kinetics of single vesicle fusion/relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 55 publications
5
56
0
2
Order By: Relevance
“…4A indicates that the apparent efficiency (E A ) of cYFP-Munc18c in complex with CFP-syntaxin 4 LE was mildly reduced from that measured with CFP-syntaxin 4. By contrast, the apparent efficiency of energy transfer between Munc18a and syntaxin 1A LE was ϳ50% lower than that measured for syntaxin 1A, a result consistent with the strong reduction in affinity conferred by the syntaxin 1A LE mutation reported in other studies (17,29). To further (Fig.…”
Section: Modeling Of Syntaxin 4 Structure and Generation Of A Constitsupporting
confidence: 87%
See 3 more Smart Citations
“…4A indicates that the apparent efficiency (E A ) of cYFP-Munc18c in complex with CFP-syntaxin 4 LE was mildly reduced from that measured with CFP-syntaxin 4. By contrast, the apparent efficiency of energy transfer between Munc18a and syntaxin 1A LE was ϳ50% lower than that measured for syntaxin 1A, a result consistent with the strong reduction in affinity conferred by the syntaxin 1A LE mutation reported in other studies (17,29). To further (Fig.…”
Section: Modeling Of Syntaxin 4 Structure and Generation Of A Constitsupporting
confidence: 87%
“…These results establish that FRET between cYFP-Munc18c and CFP-syntaxin 4 is specific to the bimolecular interaction in 3T3L1 adipocytes and sensitive to changes in Munc18c-syntaxin 4 binding affinity. Notably, CFP-syntaxin 4 localized to the plasma membrane when coexpressed with cYFPMunc18c R240L , suggesting that syntaxin 4 does not require a direct interaction with Munc18c for plasma membrane target- Our FRET experiments in adipocytes described above demonstrated a significant interaction of Munc18c with syntaxin 4 LE , which contrasts with the strongly reduced interaction reported for the LE mutant of syntaxin 1A with Munc18a in vitro and in vivo (17,29). This indicates that divergence occurs among vertebrate SM-syntaxin protein interactions.…”
Section: Modeling Of Syntaxin 4 Structure and Generation Of A Constitmentioning
confidence: 66%
See 2 more Smart Citations
“…All electron density maps were generated with a 3.2-Å resolution cutoff. another study showed that Syx1a LE is more susceptible to proteolysis (12). Direct structural data for the Munc18a-Syx1a LE complex have been lacking, however, and our data show that the LE mutant can adopt a closed conformation that tightly binds Munc18a.…”
Section: Resultsmentioning
confidence: 48%